Widespread pain and altered renal function in ME/CFS patients. Issue 3 (2nd July 2016) - McGregor, Neil R.; Armstrong, Christopher W.; Lewis, Donald P.; Butt, Henry L.; Gooley, Paul R.
ABSTRACT: Background : Widespread pain is noted in many patients with chronic fatigue syndrome (ME/CFS), fibromyalgia and temporomandibular disorders. These conditions usually start as a localized condition and spread to a widespread pain condition with increasing illness duration. Purpose : To aim was to assess the changes in biochemistry associated with pain expression and alterations in renal function. Methods : Forty-seven ME/CFS patients and age/sex-matched controls had a clinical examination, completed questionnaires, standard serum biochemistry, glucose tolerance tests and serum and urine metabolomes in an observational study. Results : Increases in pain distribution were associated with reductions in serum essential amino acids, urea, serum sodium and increases in serum glucose and the 24-hour urine volume; however the biochemistry was different for each pain area. Regression modelling revealed potential acetylation and methylation defects in the pain subjects. Conclusions : These findings confirm and extend our earlier findings. These changes appear consistent with repeated minor inflammatory-mediated alterations in kidney function resulting in essential amino acid deprivation and inhibition of protein synthesis and genetic translation within tissues.